Sleep quality, mental health and body mass index among undergraduate medical students: a cross-sectional study - Kharche, Piyush; Patle, Rupali A. (International Journal of Research in Medical Sciences, 2021)
Background: Association of sleep disorders is found cardiovascular mortality, stroke, diabetes, impaired glucose tolerance, immune dysfunction, endocrine impairments, and psychiatric morbidities including depression. Sleep quality affects college students physical and psychological health. Thus, poor sleep quality is a serious problem in college students. This study was done to assess the quality of sleep among undergraduate medical college students, to explore relationship between quality of sleep and body mass index, to study relationship between quality of sleep and anxiety, to study relationship between quality of sleep and depression. Methods: Total 300 medical students were selected by systematic random sampling method i.e. 25 students from each year studying in 3 government medical college were selected. A descriptive questionnaire for all socio-demographic parameters along with validated instrument i.e. for sleep quality, Pittsburgh sleep quality index (PSQI), for anxiety Hamilton anxiety rating scale and for depression, Becks depression inventory were used for the data collection instruments. Results: Amongst the 300 subjects 189 (63.00%) were found to be poor sleepers. The sleep quality was poor among the subjects who are in final academic year though the difference was not statistically significant (c²=2.78, df=3, p=0.4267). It was found that sleep quality was decreased among overweight and obese persons, but the difference was not statistically significant. (c²=4.657, df=2, p=0.0974). Prevalence of anxiety was found to be more in poor sleepers. Depression was also more common among the poor sleepers and the difference was statistically significant. Conclusions: Poor sleep quality was associated with depression and anxiety in students.